Analysis Of The Quality Of Learning Achieved Through The Application Of The Inquiry Base Learning Model And Its Effect On Student Learning Interest In Science Laboratory Management And Engineering Subjects - Listiono, Arsela Eko; Tukiman, Tukiman; Dilisti, Dilisti (Journal of Multidisciplinary Research, 2025)
This study aims to analyse the quality of learning achieved through the application of the inquisiry base learning (IBL) learning model and its effect on student learning interest in the Science Laboratory Management and Engineering course. The research method used is quantitative method with experimental design. The results showed that the application of the IBL model significantly improved the quality of learning, which was indicated by an increase in the average score of students. In addition, students' interest in learning also increased significantly after the application of this model. This study recommends the use of the IBL model as one of the effective approaches to improve the quality of learning and student interest in learning.